Primary and secondary prevention of cardiovascular disease in patients with hyperlipoproteinemia (a) - Grützmacher, P. (Clin Res Cardiol Suppl, 2017)
General lipoprotein (Lp) (a) screening can help to identify patients at high risk for cardiovascular disease. Non-invasive methods allow early detection of clinically asymptomatic incipient atherosclerotic disease. Medical treatment options are still unsatisfactory. Lp(a) apheresis is an established treatment in Germany for secondary prevention of progressive cardiovascular disease. Statin-based lowering of LDL cholesterol and thrombocyte aggregation inhibitors still represent the basis of medical treatment. Target levels for LDL-cholesterol should be modified in patients with hyperlipoproteinemia (a).